Parenchymal thickness: does it have an impact on outcomes of percutaneous nephrolithotomy? - Tepeler, Abdulkadir; Binbay, Murat; Akman, Tolga; Erbin, Akif; Kezer, Cem; Silay, Mesrur Selcuk; Yuruk, Emrah; Kardas, Sina; Akçay, Muzaffer; Armagan, Abdullah; Muslumanoglu, Ahmet Yaser (My University, 2023)
To evaluate whether renal parenchymal thickness (RPT) has an effect on the outcomes of percutaneous nephrolithotomy (PNL).

We performed a retrospective analysis of 144 patients with lower pole and/or renal pelvic stones who underwent PNL. The relationship between RPT and peri- and postoperative measures was evaluated.

The average age was 45.94 ± 14.47 (15-76) years. The mean BMI was calculated as 27.47 ± 4.73 (16.9-44.9) kg/m(2). The mean stone burden was 293 ± 126 (150-800 mm(2)). The mean RPT was measured as 17.33 ± 5.32 (6-35) mm. No correlation was detected between the RPT and the operation or fluoroscopy times or the duration of hospitalization (p = 0.63, 0.52, 0.08, respectively). The mean drop in hemoglobin level was 1.45 ± 1.25 (0-9) g/dl. A negative correlation was detected between hemoglobin drop and RPT (p = 0.01, r = -0.23). However, the RPT was similar in patients who did or did not require a blood transfusion (p = 0.09). The RPT was found to have no impact on success rate (p = 0.4).

The postoperative hemoglobin drop increases in parallel with the increase in RPT. However, no relationship was detected between the RPT and blood transfusion, overall success rate or any other perioperative parameters.